(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
New high-molecular sparsely cross-linked hydrogels based on carboxymethyl starch derivatives have been synthesized. The colloid-chemical properties and swelling abilities of new hydrogels in aqueous solutions, as well as their conformational transformations during the transition from one state to another have been investigated. The mutual influences of physic-chemical properties of aqueous solutions, including electrical conductivity, pH environment and swelling coefficient of hydrogels were studied. Based on the analysis of experimental results it has been established that during the ionization of new hydrogels in an aqueous environment, intramolecular associates were formed with the participation of protons and carboxylate anions, stabilized by hydrophobic interactions of the network structure of a sparsely cross-linked polyelectrolyte. It has been shown that this process was accompanied by a sharp change in pH values of the medium, increase in the electrical conductivity and the swelling coefficient of the hydrogels in water. The efficiency of new hydrogels for culturing plants on pebble-lands has been established by the field test results.